Minimal important changes of HFS-30 and HFS-7 questionnaires for patients with hemifacial spasm - Weerawat Saengphatrachai; Nutchara Inthapong; Yuvadee Pitakpatapee; Natthapon Rattanathamsakul; Prachaya Srivanitchapoom (Clinical Parkinsonism & Related Disorders)
Introduction: Hemifacial spasm (HFS) significantly reduces health-related quality of life (HRQoL). Currently, the HFS-30 and HFS-7 questionnaires are used to evaluate the HRQoL in HFS patients; however, their minimal important changes (MICs) have not yet to be established. This study aimed to determine the MICs for HFS-30 and HFS-7 and patients’ characteristics associated with them. Methods: Data were prospectively collected from HFS patients aged ≥18 years at a botulinum toxin clinic in a single tertiary university hospital between April 2022 and April 2023. We assessed HFS-30 and HFS-7 scores, Samsung Medical Center (SMC) grades, Patient Health Questionnaire-9 (PHQ-9) scores, and patient-reported HRQoL global rating of change scores at baseline, followed by assessments every two days for two weeks and at the one-month follow-up. MICs were determined based on the first follow-up visit when patients reported minimal improvement. Results: The 112 enrolled patients had a median age of 62.8 years (IQR: 56.6–69.3) and a median disease duration of 10 years (IQR: 4–17). The MICs of the HFS-30 and HFS-7 questionnaires were −4.55 points (95 % CI: −5.49 to −3.62) and −0.96 points (95 % CI: −1.28 to −0.64), respectively. Patients with moderate-to-severe depression reported significantly greater MICs than those with milder depression (p < 0.001). Patients aged less than 60 had significantly greater MICs than older patients (p = 0.045). Conclusions: The MICs of the HFS-30 and HFS-7 questionnaires were −4.55 and −0.96, respectively. The MIC is substantially greater in HFS patients with moderate-to-severe depression and younger age.